2016
DOI: 10.1158/0008-5472.can-15-2644
|View full text |Cite
|
Sign up to set email alerts
|

In SituTumor Vaccination by Combining Local Radiation and Tumor-Specific Antibody or Immunocytokine Treatments

Abstract: Interest in combining radiotherapy and immune checkpoint therapy is growing rapidly. In this study, we explored a novel combination of this type to augment anti-tumor immune responses in preclinical murine models of melanoma, neuroblastoma, and head and neck squamous cell carcinoma. Cooperative effects were observed with local radiotherapy and intratumoral injection of tumor-specific antibodies, arising in part from enhanced antibody-dependent cell-mediated cytotoxicity (ADCC). We could improve this response b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
247
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(263 citation statements)
references
References 50 publications
15
247
1
Order By: Relevance
“…However, if this strategy were to be validated, it could enable administration of this regimen of immunotherapy to those that would best benefit, and allow avoiding this somewhat toxic 5-month regimen (or using a different strategy) for those who might not benefit from this regimen. Enhancements to anti-GD2 mAb-based therapy, based on preclinical and early clinical data are being evaluated in efforts to improve its efficacy (22,2527). Since we cannot be certain that the benefit in the immunotherapy group observed for patients with KIR-ligands present or for patients with KIR2DL2+/C1+/KIR3DL1+/Bw4+ will be applicable for newer generations of anti-GD2 immunotherapeutic regimens, further studies of KIR/KIR-ligand associations with outcome in subsequent trials of immunotherapeutic regimens for children with neuroblastoma will be needed to determine the potential clinical utility of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, if this strategy were to be validated, it could enable administration of this regimen of immunotherapy to those that would best benefit, and allow avoiding this somewhat toxic 5-month regimen (or using a different strategy) for those who might not benefit from this regimen. Enhancements to anti-GD2 mAb-based therapy, based on preclinical and early clinical data are being evaluated in efforts to improve its efficacy (22,2527). Since we cannot be certain that the benefit in the immunotherapy group observed for patients with KIR-ligands present or for patients with KIR2DL2+/C1+/KIR3DL1+/Bw4+ will be applicable for newer generations of anti-GD2 immunotherapeutic regimens, further studies of KIR/KIR-ligand associations with outcome in subsequent trials of immunotherapeutic regimens for children with neuroblastoma will be needed to determine the potential clinical utility of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may in part explain these differences: cell autonomous effects resulting in greater suppression of downstream signaling, tumor-stroma crosstalk that is not recapitulated using standard in vitro culture approaches, or anti-tumor effects of ADCC in vivo (even within an immune compromised model). While the immunodeficient nude mouse is far from an ideal model for the study of antitumor immunity, these animals do produce NK cells (41) and have been used to study the role of ADCC using tumor-specific antibodies(42). We looked for tumor infiltrating immune cells by morphological analysis of H&E stained slides and CD45 IHC in cetuximab and control treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Others and we have demonstrated the cooperative interaction of combination treatment with radiation and immunotherapy in vivo . Many of these studies demonstrate that the timing and sequencing of radiation and immunotherapy may be critical for optimizing cooperative anti-tumor activity [11, 12]. Illustratively, in preclinical studies we recently demonstrated a cooperative interaction between RT and the antibody-dependent cell-mediated cytotoxicity (ADCC) response to tumor-specific monoclonal antibodies (mAb) in murine melanoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies demonstrate that the timing and sequencing of radiation and immunotherapy may be critical for optimizing cooperative anti-tumor activity [11, 12]. Illustratively, in preclinical studies we recently demonstrated a cooperative interaction between RT and the antibody-dependent cell-mediated cytotoxicity (ADCC) response to tumor-specific monoclonal antibodies (mAb) in murine melanoma [11]. This effect was enhanced using a combination of RT and immunocytokine, a fusion of the tumor-specific antibody with IL2, resulting in elimination of 5-week established tumors in most mice and a memory T cell response.…”
Section: Introductionmentioning
confidence: 99%